2021
DOI: 10.1097/qad.0000000000002914
|View full text |Cite
|
Sign up to set email alerts
|

Incident obstructive lung disease and mortality among people with HIV and a history of injecting drugs

Abstract: Objective: People with HIV (PWH) experience increased prevalence of obstructive lung disease (OLD), regardless of greater observed smoking behaviors. We investigated whether the effect of incident OLD on mortality differed by HIV and HIV viral suppression among persons who inject drugs (PWID) and report smoking history.Design: ALIVE is a longitudinal, observational cohort study of HIV-positive and seronegative PWID. This analysis included participants who had at least one spirometry measure to assess OLD betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The Examinations of HIV-associated Lung Emphysema study demonstrated that decreased DL CO and FEV 1 and airflow obstruction were independent predictors of mortality (12). Finally, incident airflow obstruction was a risk factor for mortality in the AIDS Linked to the Intravenous Experience study (13). Our finding that only the adverse DL CO phenotype was associated with increased mortality further supports diffusion impairment as a marker of excess mortality risk in HIV.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The Examinations of HIV-associated Lung Emphysema study demonstrated that decreased DL CO and FEV 1 and airflow obstruction were independent predictors of mortality (12). Finally, incident airflow obstruction was a risk factor for mortality in the AIDS Linked to the Intravenous Experience study (13). Our finding that only the adverse DL CO phenotype was associated with increased mortality further supports diffusion impairment as a marker of excess mortality risk in HIV.…”
Section: Discussionsupporting
confidence: 57%
“…Although smoking is more prevalent among PWH, human immunodeficiency virus (HIV) infection independently predicts airflow obstruction (1,2), gas exchange limitation (3)(4)(5), and emphysema (3,6). Among PWH, airflow and gas exchange abnormalities have been identified as independent risk factors for increased respiratory symptoms (7), worse respiratory health status (8), decreased functional capacity (6,9,10), and increased mortality (11)(12)(13).…”
mentioning
confidence: 99%
“…Other studies have estimated COPD prevalence, 3–5 incidence, 47 and mortality 48 49 among people who use illicit opioids, also finding a high health burden related to COPD. To our knowledge, this is the first study investigating treatment in this population.…”
Section: Discussionmentioning
confidence: 99%